The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14194160
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically and Biomechanically Relevant Monolithic Total Disc Replacement Made of 3D-Printed Thermoplastic Polyurethane

Abstract: Various implant treatments, including total disc replacements, have been tried to treat lumbar intervertebral disc (IVD) degeneration, which is claimed to be the main contributor of lower back pain. The treatments, however, come with peripheral issues. This study proposes a novel approach that complies with the anatomical features of IVD, the so-called monolithic total disc replacement (MTDR). As the name suggests, the MTDR is a one-part device that consists of lattice and rigid structures to mimic the nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…An anatomy‐based configuration‐monolithic complete disc replacement constructed of TPU 87A and TPU 95A that was successfully created by Muhammad Hanif Nadhif and his team utilizing an FDM‐based 3D printing method while maintaining tolerable fabrication error rates. The two materials were predicted to degrade at rates that would last at least 4 years 117 . The application of personalized medicine benefits a formulation's therapeutic and safety since the drug may be easily modified to the patient's weight, sex, age, and genetic information.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An anatomy‐based configuration‐monolithic complete disc replacement constructed of TPU 87A and TPU 95A that was successfully created by Muhammad Hanif Nadhif and his team utilizing an FDM‐based 3D printing method while maintaining tolerable fabrication error rates. The two materials were predicted to degrade at rates that would last at least 4 years 117 . The application of personalized medicine benefits a formulation's therapeutic and safety since the drug may be easily modified to the patient's weight, sex, age, and genetic information.…”
Section: Applicationsmentioning
confidence: 99%
“…The two materials were predicted to degrade at rates that would last at least 4 years. 117 The application of personalized medicine benefits a formulation's therapeutic and safety since the drug may be easily modified to the patient's weight, sex, age, and genetic information. Verstraete et al with the use of FDM, TPU with high cross-over point and hardness values were found as potential excipients for the production of highly drug-loaded (unmilled metformic.HCL 60%, w/w) customized dosage forms.…”
Section: Medical Sectormentioning
confidence: 99%